PENGARUH PENGGUNAAN E-LEARING DENGAN SCHOOLOGY TERHADAP HASIL BELAJAR PESERTA DIDIK - Ria Purwaningsih; Undang Rosidin; Ismu Wahyudi (Jurnal Pembelajaran Fisika, 2017)
The purpose of this study is to determine the effect of using e-Learning with schoology to students learning outcomes. The research was conducted in experimental class 1 and experimental class 2 with same initial ability so that used purposive sampling technique and quasi experimental design method with nonequivalen control group design. Both classes received blended learning and face-to-face learning with the same intensity. The result of the independent sample t-test has sig. 0.005 that means there are difference in students learning outcomes cognitive and psychomotor domains are significant between learning blended learning and face to face, with average N-gain of cognitive and psychomotor domains is 0.64 and 0.82. The conclusion of this research is the study of physics on the topic of Momentum and Impulse using e-Learning with schoology has an effect on student's learning outcomes.Tujuan penelitian ini adalah untuk mengetahui pengaruh penggunaan e-Learning dengan schoology terhadap hasil belajar peserta didik. Penelitian dilakukan pada kelas eksperimen 1 dan kelas eksperimen 2 dengan kemampuan awal yang relatif sama sehingga digunakan teknik purposive sampling dan metode quasi experimental design dengan jenis nonequivalen control group design. Kedua kelas mendapat treatment pembelajaran blended learning dan tatap muka dengan intensitas yang sama. Hasil uji independent sample t-test memiliki sig. 0,005 yang berarti terdapat perbedaan hasil belajar peserta didik ranah kognitif dan psikomotorik yang signifikan antara pembelajaran blended learning dan tatap muka, dengan rata-rata N-gain ranah kognitif dan psikomotorik sebesar 0,64 dan 0,82. Simpulan penelitian ini adalah pembelajaran fisika pada topik Momentum dan Impuls menggunakan e-Learning dengan schoology berpengaruh terhadap hasil belajar peserta didik.Kata Kunci: Blended Learning, E-Learning, Momentum dan Impuls, Schoology